PENYELESAIAN SENGKETA ADAT DI BALI (STUDI KASUS SENGKETA TANAH SETRA ANTARA DESA PAKRAMAN CEKIK DENGAN DESA PAKRAMAN GABLOGAN, KECAMATAN SELEMADEG, KABUPATEN TABANAN) - I Nyoman Adi Susila; I Ketut Wirta Griadhi; A. A. Gde Oka Parwata (Kertha Negara : Journal Ilmu Hukum, 2013)
The glowing of conflict occurred in Bali about legal action of grave field latter has given evidence that Bali in now day is far from peacefull. In solving the legal action that was occurred in Bali, the socials were more belief to the leaders in their region, such as: the leader in their village and also the leader in province. Sometimes, the means of problem solving that was taken by one of leaders was not successful. More factor of problem solving were caused successful or failed. However, that all factors could we see in standing of the law systems, legal substancy, legal structure, and legal culture.